Malnutrition prevailing trend study among under five children of urban slum area of Gwalior city Madhya Pradesh - Agarwal, Anil Kumar; Sarswat, Swati; Mahore, Ramniwas; Saraswat, Satender; Kuity, Paromita; Tripathi, Ankita (International Journal Of Community Medicine And Public Health, 2021)
Background: Under five children constitute the most vulnerable segment and their nutritional status and mortality rate is a sensitive indicator of the community’s health and nutrition. Health indices of slum children are worst among all urban groups and are even poorer than rural average. Methods: A community based cross-sectional study was conducted from October 2019 to January 2020 in urban slum area of Gwalior city. Data were collected from 550 mothers of children aged 6-60 months using pre-tested semi structured questionnaires and measuring weight, height and mid upper arm circumference of the children. Results: 68.36% of 550 children were having under nutrition in the form of underweight (53.09%), wasting (22.18%) and stunting (59.45%). Maximum number of underweight children belongs to age group 24-60 months (64.54%) followed by <24 months age groups. Stepwise regression showed that the risk of underweight and stunting was significantly (p<0.001) higher among children of illiterate mothers and children from lowest and middle households wealth index. Conclusions: Malnutrition is widely prevalent among study population more than the state and national prevalence. With increasing age cumulative increase in prevalence of malnutrition is seen perhaps due to persistence and addition of causative factors. Maternal education and faulty feeding practice are contributory factor of this high prevalence of disease.